Recent Developments and Novel Applications of Laser Shock Peening: A Review - Zhang, Chaoyi; Dong, Yalin; Ye, Chang (Advanced engineering materials, 2021)
By inducing work hardening and beneficial compressive residual stresses in near‐surface regions, laser shock peening (LSP) improves the fatigue performance of many metallic components. In recent years, LSP has found many new applications in emerging fields: additive manufacturing, ceramics, and metallic glasses. In addition, innovative process development based on LSP has been reported, which includes warm LSP, cryogenic LSP, electropulsing‐assisted LSP, laser peening without coating, femotosecond LSP, and laser peen forming. Herein, a comprehensive review of the LSP process with a focus on the novel applications and innovative process development is aimed for. The history of LSP with key events is briefly reviewed. The fundamental mechanisms of LSP, including the generation of shockwaves by a high‐energy pulsed laser, the generation of compressive residual stresses by the shockwave, and its effect on crack propagation, and how LSP induces grain refinement are also discussed. The effects of compressive residual stresses and grain refinement on the mechanical properties of metallic materials are reviewed. Recent developments in LSP, such as innovative process development based on LSP and its novel applications, are discussed. Finally, the current challenges the LSP technology faces and its future directions are also discussed. Herein, the recent developments of laser shock peening (LSP), including its applications in emerging fields, e.g., additive manufacturing and innovative process development, including warm LSP, femtosecond LSP, and electropulsing‐assisted LSP, among others, are reviewed. The current challenges the LSP technology faces and its future directions are also discussed.